IN VITRO SUSCEPTIBILITY OF CtyptOcdccus neoformans OF CLINICAL ISOLATES FROM AIDS PATIENTS: COMPARATIVE STUDY OF ETEST AND BROTH MACRODILUTION METHODS - Fernandez, Orionalda de Fatima Lisboa; Passos, Xisto Sena; Cerqueira, Carlos Henrique P.V. de; Batista, Pollyanna; Silva, Maria do Rosário Rodriguez (Revista de Patologia Tropical / Journal of Tropical Pathology, 2011)
A comparative study of Etest and broth macrodilution methods for susceptibility testing to fluconazole, ketoconazole, itraconazole and amphotericin B was conducted for sixty strains of C. neoformans isolated from Aids patients. The MICs obtained by these two methods were read after 72 hours of incubation for broth macrodilution and 48 hours for Etest. The rate agreement was obtained between the broth macrodilution and Etest methods using differences with 2 doubling dilutions. Our data showed that there was a good correlation between the MICs obtained by both methods. The correlation between these two methods tested was 96.6% (58/60), 90.0% (54/60), 93.3% (56/60) and 100% (60/60) for fluconazole, ketoconazole, itraconazole, and amphotericin B, respectively. These results indicate that Etest could be considered useful for antifungal sensitivity evaluation of yeasts in clinical laboratories.